Indigenous Languages are in Danger of Disappearance: A Study on Selected Indigenous Communities in Bangladesh (Global Journal of Human-Social Science, 2018)
This paper is to explore the challenges of our indigenous communities related to their lingual and cultural rights This explorative research utilized qualitative method including semi-structured interview and focus group discussions The findings showed that the indigenous communities of Bangladesh are facing many challenges such as educational socio-economic and political to practice their languages and culture Moreover the consequences of those challenges are related to the extinction of their languages and culture Also our state policies make the situation more critical In the future if these tendencies are going on Bangladesh will lose her multicultural and multilingual identity
Keywords: indigenous communities; lingual and cultural rights; multicultural and multilingual identity